Principles of the prolactin/vasoinhibin axis - Triebel, Jakob; Bertsch, Thomas (American journal of physiology. Regulatory, integrative and comparative physiology, 2015)
The hormonal family of vasoinhibins, which derive from the anterior pituitary hormone prolactin, are known for their inhibiting effects on blood vessel growth, vasopermeability, and vasodilation. As pleiotropic hormones, vasoinhibins act in multiple target organs and tissues. The generation, secretion, and regulation of vasoinhibins are embedded into the organizational principle of an axis, which integrates the hypothalamus, the pituitary, and the target tissue microenvironment. This axis is designated as the prolactin/vasoinhibin axis. Disturbances of the prolactin/vasoinhibin axis are associated with the pathogenesis of retinal and cardiac diseases and with diseases occurring during pregnancy. New phylogenetical, physiological, and clinical implications are discussed.
Gesehen am 10.12.2018